Long-Term Outcome of Arthrocentesis Plus Hyaluronic Acid Injection in Patients With Wilkes Stage II and III Temporomandibular Joint Internal Derangement. Issue 7 (October 2015) - Ungor, Cem; Atasoy, Kerem Turgut; Taskesen, Fatih; Pirpir, Cagasan; Yilmaz, Onur
Abstract : Objective: Arthrocentesis is a minimally invasive procedure used to manage temporomandibular joint (TMJ) internal derangement (ID). This study evaluated the outcome of arthrocentesis in patients with Wilkes stage II and III TMJ ID. Patients and Methods: This retrospective study enrolled 50 patients who underwent arthrocentesis in 2011 and 2012 at the Karadeniz Technical University, Faculty of Dentistry, Department of Oral and Maxillofacial Surgery, Turkey. In total, 43 patients underwent unilateral arthrocentesis, whereas 7 patients had bilateral arthrocentesis. The clinical parameters recorded were pain (visual analogue scale [VAS] 0–100 mm during movement), chewing function efficacy (VAS 0–100), clicking sounds, and mandibular movements, including maximum interincisal opening (MIO), lateral excursion, and protrusion. All the parameters were recorded preoperatively, and 1, 3, 6, and 24 months after treatment. Results: The MIO, lateral excursion, and protrusion were significantly greater than preoperatively in all the patients. Pain declined significantly postoperatively. The patients in Wilkes III group had greater improvement in mandibular movement and pain than the patients in Wilkes II group. Conclusion: : Arthrocentesis was reliable for treating both Wilkes II and III TMJ ID, and the treatment results were better in Wilkes III patients.